Security and privacy concerns in the Malaysian national IoT strategic roadmap: legal response and the way forward - Sidi Ahmed, Sidi Mohamed; Zulhuda, Sonny (Universiti Utara Malaysia (UUM), 2021)
Malaysia is geared to maximizing the digital technology and Internet of Things to reap the full benefit of the digital economy. In 2014, the Government came up with an important policy document entitled the National Internet of Things (IoT) Strategic Roadmap (‘The Roadmap). Hopes are mounting that the IoT will be smoothly and speedily adopted in Malaysia amid various concerns relating to data security and data privacy. This paper investigates how the Roadmap frames the concerns of data security and privacy vis a vis the IoT in Malaysia. Employing a doctrinal and library research, this paper finds that while the Roadmap complements or supports the existing legal framework, its objectives will only be achieved if those legal requirements are complied with.